Repositioning of Religious Courts in Resolving Bankruptcy Disputes in Islamic Banking - Arimba, Cahya Iradi; Suganda, Rangga (Electronic Journal of Education, Social Economics and Technology, 2025)
The repositioning of the Religious Court in handling Islamic banking bankruptcy cases in Indonesia is still a topic of discussion in the community. This is inseparable from the fact that there is still a difference between regulation and reality. Given that so far the resolution of Islamic banking bankruptcy disputes is still the field of authority of the Commercial Court, which should and should have been resolved under the authority of the Religious Court. Many broad and complex dimensions become the benchmark for why bankruptcy in Islamic banking should be resolved under the Religious Court, there are at least three aspects that can be studied, namely, covering philosophical, sociological, and juridical aspects. This research aims to analyse the philosophical, sociological and juridical bases of the repositioning and its implications for legal protection for debtors and creditors in Islamic banking insolvency cases. Philosophically, this repositioning seeks to uphold the principle of justice contained in Islamic law, where the principle of al-adl (justice) is the basis for resolving economic cases, including in the context of Islamic banking. From a sociological perspective, this repositioning is a response to public demand for a legal system that better reflects sharia values. Juridically, this repositioning is based on existing regulations, namely Law No. 3 of 2006 on Religious Courts and Law No. 21 of 2008 on Islamic Banking and Supreme Court Regulation (Perma) No.14 of 2016 on Procedures for Settling Sharia Economic Disputes, which gives the Religious Courts the authority to handle sharia economic cases. The implications of this repositioning include better legal protection for debtors and creditors, increased accountability and transparency in settlements, and increased legal certainty in the Islamic banking sector. This repositioning is expected to strengthen the integration between sharia law and state law, create a fairer, more transparent, and equitable justice system for all parties involved, and increase public confidence in the Islamic banking system in Indonesia.